Constrained robust adaptive control for vehicle active suspension systems. (2015) - Pan, Huihui; Sun, Weichao; Gao, Huijun; Hayat, Tasawar; Alsaadi, Fuad
In this paper, a constrained robust adaptive control strategy is presented for active suspension systems in the presence of non-symmetric input saturations, whose objective is to stabilise the attitude of the vehicle and improve ride comfort. In particular, by means of command filtering idea, an auxiliary system is constructed to reduce the negative effects caused by possible saturations, and the following stability proof ensures the theoretical strictness. Furthermore, the proposed constrained robust adaptive control approach is applied to a quarter-car active suspension system, where nonlinear spring and piecewise linear damper are adopted. Finally, a numerical example simulation with typical periodic road input is conducted to verify the effectiveness of the theoretic results obtained.